Issues in Engineering Geological Classification of Weathered Sedimentary Rocks: Case Study of Kati Formation, Parit, Perak - Mang, Wong Jia; Rafek, Abdul Ghani Md; Lai, Goh Thian (International Journal of Engineering and Technology, 2018)
Kati Formation consists of alternating layers of sandstone, siltstone and mudstone that results in non-uniform weathering. The presence of surficial features due to weathering such as iron bands, iron recementation, iron staining and lithobionts coating in an uneven distribution on the outcrop causing more complexity to the heterogeneous sedimentary rocks which are also tectonically deformed. The presence of iron recementation in highly weathered rocks causing the rock strength to be higher than the moderately weathered rocks. Thus, several laboratory tests are conducted in this study to characterise the weathered rocks which are uniaxial compressive strength (UCS), point load strength index, slake durability test, jar slake test and Schmidt hammer rebound test. Among the laboratory tests conducted in this study, slake durability index test, Id2 is the ideal test to characterise the rock samples of different weathering grades as it gives a large range of laboratory test results which is 0.3 % to 15.0 % for completely weathered, 22.0 % to 67.0 % for highly weathered, 68.0 % to 83.0 % for moderately weathered and 87.0 to 98.0 % for slightly weathered to fresh rocks. The values obtained are not affected by the uneven distribution of iron oxide present in the rock samples.